Africa Multiple: Interview with Kenyan poet and scholar Abdilatif Abdalla (Workshop Intermedial Indian Ocean - 2021, 2021)
Abdilatif Abdalla who was in Bayreuth as guest for the series of events on the Indian Ocean, in conversation with Clarissa Vierke, Professor of Literatures in African Languages at the University of Bayreuth. Abdilatif Abdalla is a Kenyan poet, publicist and university lecturer and considered one of the best-known Swahili poets of the present day. Since 1995, Abdalla has taught Swahili at the University of Leipzig.